AD, Volume 15, n° 2, 1990 - Full Issue - journal system (Africa Development, 1990)
Contents L'administration sénégalaise et la gestion des "fléaux sociaux" Momar Coumba Diop ............................... 5 Population et Villes Sénégal: La croissance démogéographique Amadou Diop ............................ 33 Family Planning: A Human Right for Women Stella C. Ogbuago ......................... 45 The Crisis of Development Finance and Its Impact on Developing Economies: Trends, Issues and Policy Options Daniel Smart Asante-Odame ......................... 57 Organized Labour Under the Military Regimes in Nigeria Austin Isamah ................................ 81 Diamond Mining and Underdevelopment in Sierra Leone 1930/1980 Babatunde Zack-Williams ........................... 95 Book Reviews The Subvention of the Invention of Africa Kwesi Prah ................................ 119 Reinventing Africa? Ernest Harsch ............................... 131